2019
DOI: 10.1148/radiol.2019182321
|View full text |Cite
|
Sign up to set email alerts
|

CT-guided Lung Biopsy: Effect of Biopsy-side Down Position on Pneumothorax and Chest Tube Placement

Abstract: Background: Supine or prone positioning of the patient on the gantry table is the current standard of care for CT-guided lung biopsy; positioning biopsy side down was hypothesized to be associated with lower pneumothorax rate.Purpose: To assess the effect of positioning patients biopsy side down during CT-guided lung biopsy on the incidence of pneumothorax, chest drain placement, and hemoptysis. Materials and Methods:This retrospective study was performed between January 2013 and December 2016 in a tertiary re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 37 publications
3
45
3
Order By: Relevance
“…A recent meta-analysis reported that normal saline tract sealant, a rapid needleout patient-rollover approach (74), and the use of a tract plug or blood patch reduced the likelihood of pneumothorax requiring tube drainage (75). One study reported that positioning the patient with the biopsy side down could reduce pneumothorax incidence after PTNB (76).…”
Section: Summary Of Guidelines and Commentsmentioning
confidence: 99%
“…A recent meta-analysis reported that normal saline tract sealant, a rapid needleout patient-rollover approach (74), and the use of a tract plug or blood patch reduced the likelihood of pneumothorax requiring tube drainage (75). One study reported that positioning the patient with the biopsy side down could reduce pneumothorax incidence after PTNB (76).…”
Section: Summary Of Guidelines and Commentsmentioning
confidence: 99%
“…According to the literature, cases of postpunction hemoptysis vary between 1.7-10.3% (ref. 3,[15][16][17][18] ). Our results are in agreement with the reported numbers of both minor and severe complicating PNOs as well as the number of patients with hemoptysis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some authors promote a lateral position of the patient with the lung to be punctured pointing downwards during the biopsy procedure 32,33 . This is a method not generally endorsed at our institution because we think that the position that allows the best access to the pulmonary target lesion and at the same time is most comfortable for the patient, thus ensuring the best compliance and minimising movement, outweigh the potential benefits from a lateral position with the punctured lung pointing downwards.…”
Section: Discussionmentioning
confidence: 99%